Oligomerization-driven avidity correlates with SARS-CoV-2 cellular binding and inhibition - Asor, R (University of Oxford, 2024)
Mass photometry data and analysis code presented in the pablication "Oligomerisation-driven avidity controls SARS-CoV-2 cellular binding and inhibition"